Writing the Structures of Landholding in a Changing Italy (5th–8th century). The PRIN project LEXICONOMY - Paolo Tomei; Dario Internullo (Studi di Storia Medioevale e di Diplomatica: Nuova Serie)
The article illustrates the PRIN 2022 project PNRR Lexiconomy. Writing the structures of landholding in a changing Italy (5th-8th centuries), directed by Paolo Tomei and co-directed by Dario Internullo. The aim of the project is to investigate the centuries of transition from Antiquity to the Middle Ages in Italy (5th-8th centuries) from the point of view of the landed property lexicon, whose dynamics, between continuity and transformation, is considered here as a historical phenomenon worthy of scientific analysis.